Resin composition, composite material, and molded article

The resin composition, featuring an aromatic polyether with a specific radical content and an interface reinforcing agent, addresses the challenge of achieving high interfacial shear strength with reinforced fibers, resulting in enhanced mechanical properties for the composite material.

JP2025070828APending Publication Date: 2025-05-02IDEMITSU KOSAN CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023181389
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Conventional resin compositions and composite materials face challenges in achieving excellent interfacial shear strength with reinforced fibers, as existing technologies do not adequately address this issue.

Method used

A resin composition comprising an aromatic polyether with a specific radical amount and an interface reinforcing agent, which enhances the interfacial shear strength by forming a structure with improved adhesion to the reinforcing fibers.

Benefits of technology

The proposed resin composition and composite material exhibit excellent interfacial shear strength and mechanical properties, such as tensile strength, due to the combined effect of the aromatic polyether and the interface reinforcing agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070828000001
    Figure 2025070828000001
  • Figure 2025070828000002
    Figure 2025070828000002
  • Figure 2025070828000003
    Figure 2025070828000003
Patent Text Reader

Abstract

To provide a resin composition, a composite material, and a molded article, exhibiting excellent interfacial shear strength against reinforcing fibers.SOLUTION: A resin composition comprises an aromatic polyether (A), whose radical quantity at 25°C is 6.5×1015 to 9.0×1017 spin / g, as measured using TEMPOL as a standard substance and benzene as a solvent for the standard substance, and 0.05 to 1.0 pt.mass of an interfacial strength enhancer (B) based on 100 pts.mass of the aromatic polyether (A).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a composite material, and a molded article. Specifically, the present invention relates to a resin composition, a composite material, and a molded article that are excellent in interfacial shear strength with reinforcing fibers. [Background technology]

[0002] Patent Document 1 discloses that a specific aromatic polyether produced by causing a component having a specific polymerization catalytic activity to be present in a reaction system is mixed with a reinforcing material or filler such as glass fiber, carbon fiber, aramid fiber, calcium carbonate, or calcium silicate. Patent Document 2 discloses that a phosphate is blended into a polyarylene ether ketone-based composition in order to stabilize the composition against thermal oxidation (to suppress changes in melt viscosity over time). Non-Patent Document 1 discloses the use of two types of antioxidants (a phenol-based antioxidant and a phosphorus-based antioxidant) in order to improve the stability of polyether ether ketone (PEEK). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 64-065129 [Patent Document 2] Patent Publication No. 2023-60050 [Non-patent literature]

[0004] [Non-Patent Document 1] Journal of Macromolecular Science, Part A: Pure and Applied Chemistry (2012) 49, 571-577 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in conventional techniques including Patent Documents 1 and 2 and Non-Patent Document 1, there is room for further improvement in terms of improving the interfacial shear strength of the resin composition with the reinforcing fibers.

[0006] An object of the present invention is to provide a resin composition, a composite material, and a molded article that are excellent in interfacial shear strength with reinforcing fibers. [Means for solving the problem]

[0007] As a result of extensive research, the present inventors have found that a resin composition containing an aromatic polyether having a specific radical amount and an interfacial strengthening agent has excellent interfacial shear strength with reinforcing fibers, and have completed the present invention. According to the present invention, the following resin composition and the like can be provided. 1. The standard substance was TEMPOL and the solvent for the standard substance was benzene. The amount of radicals at 25°C was 6.5 x 10 15 ~9.0×10 17 A resin composition comprising: an aromatic polyether (A) having a spin / g ratio; and 0.05 to 1.0 part by mass of an interface reinforcer (B) relative to 100 parts by mass of the aromatic polyether (A). 2. The standard substance was TEMPOL and the solvent for the standard substance was benzene. The amount of radicals at 25°C was 6.5 x 10 15 ~9.0×10 17 2. The resin composition according to 1, wherein the resin composition has a molecular weight of 1.5 or more and a molecular weight of 2.5 or more. 3. The resin composition according to 1 or 2, wherein the aromatic polyether (A) is a polyarylene ether ketone. 4. The resin composition according to any one of 1 to 3, wherein the aromatic polyether (A) comprises at least one member selected from the group consisting of polyether ether ketone (PEEK), polyether ketone ketone (PEKK) and polyether ketone (PEK). 5. The resin composition according to any one of 1 to 4, wherein the interface reinforcer (B) comprises at least one compound selected from the group consisting of phosphoric acid compounds, phenolic compounds, amine compounds and sulfur-based compounds. 6. A composite material comprising the resin composition according to any one of 1 to 5, and 0.01 to 500 parts by mass of reinforcing fibers (C) per 100 parts by mass of the resin composition. 7. The composite material according to 6, wherein the reinforcing fibers (C) comprise at least one type selected from the group consisting of carbon fibers, glass fibers and aramid fibers. 8. The composite material according to 6 or 7, wherein the average fiber length of the reinforcing fibers (C) in the composite material is 5 mm or more. 9. A molded article comprising the resin composition according to any one of 1 to 5. 10. A molded article comprising the composite material according to any one of 6 to 8. 11. The molded article according to 9 or 10, which is an injection molded article. 12. The molded article according to 9 or 10, which is an extrusion molded article. 13. The molded body according to 9 or 10, which is a compression molded body. Effect of the Invention

[0008] According to the present invention, it is possible to provide a resin composition, a composite material, and a molded article which are excellent in interfacial shear strength with reinforcing fibers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The resin composition, composite material, and molded article of the present invention will be described in detail below. In this specification, "x to y" represents a numerical range of "not less than x and not more than y." The upper and lower limit values ​​described in relation to the numerical ranges can be combined in any combination. In addition, among the individual embodiments of the aspects of the present invention described below, it is possible to combine two or more embodiments that are not mutually contradictory, and an embodiment combining two or more embodiments is also an embodiment of the aspects of the present invention.

[0010] 1.Resin composition The resin composition according to one embodiment of the present invention has a radical amount of 6.5×10 at 25° C., measured using TEMPOL as a standard substance and benzene as a solvent for the standard substance. 15 ~9.0×10 17 and 0.05 to 1.0 part by mass of an interface strengthening agent (B) relative to 100 parts by mass of the aromatic polyether (A). The resin composition according to this embodiment has an excellent effect of providing excellent interfacial shear strength to the reinforcing fibers. Although the reason why such an effect is obtained is not necessarily clear, it is presumed that a new structure having an adhesive effect on the reinforcing fiber is formed by the combined effect of the interfacial reinforcing agent (B) and a part of the radicals of the aromatic polyether (A). Here, the interfacial reinforcing agent (B) may act as a radical scavenger and part of it may react with the aromatic polyether. In addition, the radical amount is 6.5 × 10 15 ~9.0×10 17 The aromatic polyether (A) having a high concentration of 10 ...

[0011] (Aromatic polyether (A)) In one embodiment, the radical content of the aromatic polyether (A) is 6.5×10 15 spin / g or more, 10×10 15 spin / g or more, 20×10 15 spin / g or more, 30×10 15 spin / g or more, 40×10 15 spin / g or more or 50×10 15 spin / g or more, and 9.0×10 17 spin / g or less, 5.0×10 17spin / g or less or 1.0×10 17 spin / g or less. The amount of radicals in aromatic polyether (A) is 6.5×10 15 If the spin / g is less than this, the above-mentioned composite effect is difficult to obtain, and the interfacial shear strength with the reinforcing fiber is not sufficiently obtained. 17 If it exceeds spin / g, the thermal stability is insufficient and the molded article does not exhibit sufficient mechanical properties.

[0012] The radical amount of the aromatic polyether (A) can be increased to the above-mentioned range, for example, by using a monomer containing a chlorine atom as a reactive group (e.g., 4,4'-dichlorobenzophenone, etc.) as a monomer when synthesizing (polymerizing) the aromatic polyether (A). The radical amount of the aromatic polyether (A) is a value measured by the method described in the Examples.

[0013] In one embodiment, the aromatic polyether (A) is a polyarylene ether ketone. In one embodiment, the aromatic polyether (A) comprises one or more selected from the group consisting of polyetheretherketone (PEEK), polyetherketoneketone (PEKK) and polyetherketone (PEK). In one embodiment, the aromatic polyether (A) comprises polyetheretherketone (PEEK).

[0014] In one embodiment, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, 99% by mass or more, 99.5% by mass or more, or substantially 100% by mass of the aromatic polyether (A) is one or more selected from the group consisting of polyetheretherketone (PEEK), polyetherketoneketone (PEKK), and polyetherketone (PEK). In one embodiment, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, at least 97% by weight, at least 99% by weight, at least 99.5% by weight, or substantially 100% by weight of the aromatic polyether (A) is polyetheretherketone (PEEK).

[0015] In one embodiment, the aromatic polyether (A) contains a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2). [ka]

[0016] In one embodiment, the aromatic polyether (A) contains a structural unit represented by the following formula (3): [ka]

[0017] The structural unit represented by formula (3) is a linkage between a structural unit represented by formula (1) and a structural unit represented by formula (2).

[0018] In one embodiment, the aromatic polyether (A) does not contain any other structure than the structural units represented by formula (1) and formula (2).

[0019] In one embodiment, the aromatic polyether (A) contains structures other than the structural units represented by formula (1) and formula (2) within a range that does not impair the effects of the present invention.

[0020] In one embodiment, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, 99% by mass or more, 99.5% by mass or more, or substantially 100% by mass of the aromatic polyether (A) are structural units represented by formula (1) and structural units represented by formula (2), or structural units represented by formula (3).

[0021] In one embodiment, in the aromatic polyether (A), the molar ratio of the structural unit represented by formula (1) to the structural unit represented by formula (2) (structural unit represented by formula (1) : structural unit represented by formula (2)) is 47.5:52.5 to 52.5:47.5, 48.0:52.0 to 52.0:48.0, 48.5:51.5 to 51.5:48.5, 49.0:51.0 to 51.0:49.0, or 49.5:50.5 to 50.5:49.5. The number of moles of the structural unit represented by formula (1) may be larger than, smaller than, or the same as the number of moles of the structural unit represented by formula (2).

[0022] The terminal structure of the main chain of the aromatic polyether (A) is not particularly limited. In one embodiment, the structural unit represented by formula (1) is disposed at one or more ends of the main chain of the aromatic polyether (A). In this case, the end structure bonded to the structural unit may be a halogen atom. The halogen atom may be, for example, a chlorine atom (Cl) or a fluorine atom (F). In one embodiment, the structural unit represented by formula (2) is disposed at one or more ends of the main chain of the aromatic polyether (A). In this case, the end structure bonded to the structural unit may be, for example, a hydrogen atom (H) or the like (when the end structure is a hydrogen atom (H), a hydroxyl group is formed together with the oxygen atom (O) in the structural unit). The terminal structure of the aromatic polyether (A) may be, for example, a structure in which the above-mentioned halogen atom or hydroxyl group is replaced with a hydrogen atom (H), etc. The terminal structure may have a structure other than those exemplified above.

[0023] The melt flow rate of the aromatic polyether (A) is not particularly limited. In one embodiment, the melt flow rate of the aromatic polyether (A) is 1500 g / 10 min or less, 1000 g / 10 min or less, 500 g / 10 min or less, 300 g / 10 min or less, 200 g / 10 min or less, 100 g / 10 min or less, 80 g / 10 min or less, or 60 g / 10 min or less, and is 0.0001 g / 10 min or more, 0.0005 g / 10 min or more, or 0.001 g / 10 min or more. The aromatic polyether (A) has a melt flow rate of, for example, 0.001 to 500 g / 10 min, preferably 0.01 to 100 g / 10 min from the viewpoint of mechanical properties, and more preferably 0.1 to 50 g / 10 min from the viewpoint of moldability. The melt flow rate of the aromatic polyether (A) is a value measured by the method described in the Examples.

[0024] (Interfacial strengthener (B)) In this specification, the term "interfacial reinforcing agent" means an agent capable of improving the interfacial shear strength between the aromatic polyether (A) and the reinforcing fibers. In one embodiment, the interface strengthener (B) includes one or more selected from the group consisting of phosphoric acid compounds, phenolic compounds, amine compounds, and sulfur-based compounds. This allows the effects of the present invention to be exhibited more satisfactorily.

[0025] Examples of the phosphoric acid compound include triphenyl phosphite (available as "JP-360" manufactured by Johoku Chemical Co., Ltd.), trisnonylphenyl phosphite (available as "JP-351" manufactured by Johoku Chemical Co., Ltd.), tricresyl phosphite (available as "JP-3CP" manufactured by Johoku Chemical Co., Ltd.), tris(2-ethylhexyl)phosphite (available as "JP-308E" or "JPE-308E" manufactured by Johoku Chemical Co., Ltd.), tridecyl phosphite (available as "JP-310" manufactured by Johoku Chemical Co., Ltd.), trilauryl phosphite (available as "JP-312L" manufactured by Johoku Chemical Co., Ltd.), tris(tridecyl)phosphite (available as "JP-333E" manufactured by Johoku Chemical Co., Ltd.), and available as "JPM-308" from Johoku Chemical Co., Ltd.), diphenyl monodecyl phosphite (available as "JPM-311" from Johoku Chemical Co., Ltd.), diphenyl mono(tridecyl) phosphite (available as "JPM-313" from Johoku Chemical Co., Ltd.), tetraphenyl dipropylene glycol diphosphite (available as "JPP-100" from Johoku Chemical Co., Ltd.), tetra(C12-C15 alkyl)-4,4'-isopropylidene diphenyl diphosphite (available as "JA-805" from Johoku Chemical Co., Ltd.), 4,4'-butylidene bis(3-methyl-6-t-butylphenyl ditridecyl phosphite) (available from Johoku Chemical Co., Ltd. as "JPH-1200"), a mixture of bis(tridecyl)pentaerythritol diphosphite and bis(nonylphenyl)pentaerythritol diphosphite (available from Johoku Chemical Co., Ltd. as "JPP-88"), bis(decyl)pentaerythritol diphosphite (available from Johoku Chemical Co., Ltd. as "JPE-10"), bis(tridecyl)pentaerythritol diphosphite (available from Johoku Chemical Co., Ltd. as "JPE-13R"), tristearyl phosphite (available from Johoku Chemical Co., Ltd. as "JPE-318E"), distearyl pentaerythritol diphosphite (available from Johoku Chemical Co., Ltd. as "JPP-2000PT"), tris(2,4-Di-tert-butylphenyl)phosphite (available from Johoku Chemical Co., Ltd. as "JP-650"), hydrogenated bisphenol A·pentaerythritol phosphite polymer (available from Johoku Chemical Co., Ltd. as "JPH-3800"), diethyl (3,5-di-t-butyl-4-hydroxybenzyl)phosphonate (available from Johoku Chemical Co., Ltd. as "JC-356"), 3,9-Bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-dipho sphaspiro「5.5」undecane (available as "ADEKA STAB PEP-8" manufactured by ADEKA CORPORATION), 3,9-Bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro「5.5」undecane (available as "ADEKA STAB PEP-36" manufactured by ADEKA CORPORATION), 2,2'-Methylenebis(4,6-di-tert-butylphenyl) 2-ethylhexyl phosphite (available as "ADK STAB HP-10" manufactured by Adeka Corporation), Tris(2,4-ditert-butylphenyl) phosphite (available as "ADK STAB 2112" / "ADK STAB 2112RG" manufactured by Adeka Corporation), Tris(nonylphenyl) phosphite (available as "ADK STAB 1178" manufactured by Adeka Corporation), Tetra-C12-15-alkyl (propane-2,2-diylbis(4,1-phenylene)) bis(phosphite) (available as "ADK STAB 1500" manufactured by Adeka Corporation), 2-Ethylhexyl diphenyl phosphite (available as "ADK STAB 135A" manufactured by Adeka Corporation), Triisodecyl phosphite (available as "ADK STAB 3010" manufactured by Adeka Corporation), Triphenyl phosphite (available as "ADEKA STAB TPP" manufactured by ADEKA Corporation), 2-Ethylhexyl diphenyl phosphite (available as "ADEKA STAB C" manufactured by ADEKA Corporation), Bis-(2,4-di-tert-butyl-phenyl)-phosphiterythritol diphosphite (available as "Ultranox 626" manufactured by SI Corporation) and the like.

[0026] Examples of phenol compounds include 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (available as "ADEKA STAB AO-20" manufactured by Adeka Corporation), 4,4',4''-(1-methylpropanyl-3-ylidene)tris(6-tert-butyl-m-cresol) (available as "ADEKA STAB AO-30" manufactured by Adeka Corporation), 6,6'-di-tert-butyl-4,4'-butylidenedi-m-cresol (available as "ADEKA STAB AO-40" manufactured by Adeka Corporation), Octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (available as "ADEKA STAB AO-50" manufactured by Adeka Corporation), and Pentaerythritol. tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (available as "ADEKA STAB AO-60" from Adeka Corporation), 3,9-Bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane (available as "ADEKA STAB AO-80" from Adeka Corporation), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxyphenylmethyl)-2,4,6-trimethylbenzene (available as "ADEKA STAB AO-330" from Adeka Corporation), styrenated phenol (available as "NOCRAC SP, SP-N" from Ouchi Shinko Chemical Industry Co., Ltd.), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol) (available as "NOCRAC NS-5" from Ouchi Shinko Chemical Industry Co., Ltd.), 2,2'-methylenebis(4-methyl-6-tert-butylphenol) (available as "NOCRAC NS-6" from Ouchi Shinko Chemical Industry Co., Ltd.), 4,4'-butylidenebis(6-tert-butyl-m-cresol) (available as "NOCRAC NS-30" from Ouchi Shinko Chemical Industry Co., Ltd.), 4,4'-thiobis(3-methyl -6-tert-butylphenol) (available as "Nocrac 300" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), butylated reaction product of p-cresol and dicyclopentadiene (available as "Nocrac PBK" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 2,5-di-tert-butylhydroquinone (available as "Nocrac NS-7" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 2,6-di-tert-butyl-4-methylphenol (available as "Nocrac 200 Crystal" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), etc.

[0027] Examples of the amine compound include a reaction product of diphenylamine and acetone (available as "Nocrac B, BN" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), N-phenyl-1-naphthylamine (available as "Nocrac PA" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), alkylated diphenylamine (available as "Nocrac ODA, ODA-N" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), octylated diphenylamine (available as "Nocrac AD-F" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 4,4'-bis(α,α-dimethylbenzyl)diphenylamine (available as "Nocrac CD" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), p-(p-toluenesulfonylamido)diphenylamine (available as "Nocrac TD" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), N,N'-di-2-naphthyl-p-phenylenediamine (available as "Nocrac White" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), N-isopropyl -N'-p-phenylenediamine (available as "Nocrac 810-NA" from Ouchi Shinko Chemical Industry Co., Ltd.), N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (available as "Nocrac 6C" from Ouchi Shinko Chemical Industry Co., Ltd.), N-(3-methacryloyloxy-2-hydroxypropyl)-N'-phenyl-p-phenylenediamine (available as "Nocrac G-1" from Ouchi Shinko Chemical Industry Co., Ltd.), 2,2,4-trimethyl-1,2-dihydroquinoline polymer (available as "Nocrac 224" from Ouchi Shinko Chemical Industry Co., Ltd.), (224-S)" from Ouchi Shinko Chemical Industry Co., Ltd.), 6-ethoxy-1,2-dihydro-2,2,4-trimethylquinoline (available as "Nocrac AW, AW-N" from Ouchi Shinko Chemical Industry Co., Ltd.), Tetrakis(2,2,6,6-tetramethyl-4-piperidyl) butane-1,2,3,4-tetracarboxylate (available as "ADEKA STAB LA-57" from Adeka Corporation), Tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl) butane-1,2,3,4-tetracarboxylate (available as "ADEKA STAB LA-52" from Adeka Corporation), 1,2,3,4-Butanetetracarboxylic acid, tetramethyl ester, reaction products with 1,2,2,6,6-pentamethyl-4-piperidinol and be-ta,be-ta,be-ta',be-ta'-tetramethyl-2,4,8,10-tetraoxaspiro「5.5」undecane-3,9-diethanol (available as "ADEKA STAB LA-63P" manufactured by ADEKA CORPORATION), 1,2,3,4-Butanetetracarboxylic acid, tetramethyl ester, reaction products with 2,2,6,6-tetramethyl-4-piperidinol and be-ta,be-ta,be-ta',be-ta'-tetramethyl-2,4,8,10-tetraoxaspiro「5.5」undecane-3,9-diethanol (available as "ADEKA STAB LA-68" manufactured by ADEKA CORPORATION), Bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate (available as "ADEKA STAB LA-72" from Adeka Corporation), Bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate (available as "ADEKA STAB LA-77Y" / "ADEKA STAB LA-77G" from Adeka Corporation), Bis(1-undecanoxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate (available as "ADEKA STAB LA-81" from Adeka Corporation), 1,2,2,6,6-Pentamethyl-4-piperidyl methacrylate (available as "ADEKA STAB LA-82" from Adeka Corporation), 2,2,6,6-Tetramethyl-4-piperidyl methacrylate (available as "ADEKA STAB LA-87" from Adeka Corporation), 2,2,6,6-tetramethylpiperidin-4-yl hexadecanoate2,2,6,6-tetramethylpiperidin-4-yl octadecanoate (available as "ADK STAB LA-40MP" or "ADK STAB LA-40Si" manufactured by Adeka Corporation).

[0028] Examples of sulfur-based compounds include 2-mercaptobenzimidazole (available as "Nocrac MB" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 2-mercaptomethylbenzimidazole (available as "Nocrac MMB" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), zinc salt of 2-mercaptobenzimidazole (available as "Nocrac MBZ" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), nickel dibutyldithiocarbamate (available as "Nocrac NBC-P (NBC)" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), dilauryl thiodipropionate (available as "Nocrac 400" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 2,2-Bis{"3-(dodecylthio)-1-oxopropoxy"methyl}propane-1,3-diyl Examples of such bis(3-(dodecylthio)propionate) (available as "ADK STAB AO-412S" manufactured by Adeka Corporation), (available as "ADK STAB AO-412S" manufactured by Adeka Corporation), and Di(tridecyl) 3,3'-thiodipropionate (available as "ADK STAB AO-503" manufactured by Adeka Corporation). In one embodiment, the sulfur-based compound is a compound that is not a diphenylsulfone or a compound that is not a diarylsulfone.

[0029] In one embodiment, the interfacial enhancing agent (B) is a compound that reacts with radicals. By "reacts with radicals" is meant to chemically bond (covalently bond) with the radicals or to chemically react with the radicals to transform the radical species.

[0030] The content of the interface reinforcement agent (B) in the resin composition is, relative to 100 parts by mass of the aromatic polyether (A), 0.05 parts by mass or more, 0.10 parts by mass or more, 0.15 parts by mass or more, or 0.20 parts by mass or more, and is 1.0 part by mass or less, 0.80 parts by mass or less, 0.50 parts by mass or less, or 0.30 parts by mass or less. If the content of the interfacial reinforcement agent (B) is less than 0.05 parts by mass, the effect as an interfacial reinforcement agent is insufficient, and if the content of the interfacial reinforcement agent (B) is more than 1.0 parts by mass, there is a concern that the mechanical properties of the molded article may be deteriorated.

[0031] The resin composition may contain components other than the aromatic polyether (A) and the interface reinforcer (B) as long as the effects of the present invention are not impaired. Examples of the other components include resins other than the aromatic polyether (A). Examples of the other resins include fluororesins such as polytetrafluoroethylene. As the other components, one type may be used alone, or two or more types may be used in combination.

[0032] In one embodiment, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, at least 97% by weight, at least 99% by weight, at least 99.5% by weight, or substantially 100% by weight of the resin composition is the aromatic polyether (A) and the interfacial reinforcer (B). Incidentally, in the case of "substantially 100% by mass", unavoidable impurities may be contained.

[0033] The contents of each component in the resin composition explained above can also be applied to the blending amounts of each component when preparing the resin composition. The radical amount of the aromatic polyether (A) explained above can also be applied as the radical amount of the aromatic polyether (A) during preparation of the resin composition (immediately before mixing with the interface reinforcing agent (B)). Furthermore, the radical amount of the aromatic polyether (A) described above can also be applied as the radical amount per unit mass of the resin composition. That is, in one embodiment, the resin composition has a radical amount of 6.5×10 at 25° C., measured using TEMPOL as a standard substance and benzene as a solvent for the standard substance. 15 ~9.0×10 17 spin / g.

[0034] 2.Composite materials A composite material according to an embodiment of the present invention contains the resin composition according to an embodiment of the present invention and 0.01 to 500 parts by mass of reinforcing fibers (C) relative to 100 parts by mass of the resin composition. According to the composite material of this embodiment, the interfacial shear strength between the resin composition and the reinforcing fibers is excellent, and therefore the effect of having excellent mechanical strength (for example, tensile strength) as a composite material can be obtained.

[0035] In one embodiment, the content of the reinforcing fiber (C) in the composite material is 0.01 parts by mass or more, 0.1 parts by mass or more, 1 part by mass or more, or 10 parts by mass or more, and 500 parts by mass or less, 300 parts by mass or less, 200 parts by mass or less, or 100 parts by mass or less, relative to 100 parts by mass of the resin composition.

[0036] In one embodiment, the reinforcing fibers (C) include one or more selected from the group consisting of carbon fibers, glass fibers, and aramid fibers. In one embodiment, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, 99% by mass or more, 99.5% by mass or more, or substantially 100% by mass of the reinforcing fibers (C) are one or more types selected from the group consisting of carbon fibers, glass fibers, and aramid fibers.

[0037] In one embodiment, the carbon fibers include one or more selected from the group consisting of PAN-based carbon fibers, pitch-based carbon fibers, thermoset-based carbon fibers, phenolic-based carbon fibers, vapor-grown carbon fibers, and recycled carbon fibers (RCF). In one embodiment, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, 99% by mass or more, 99.5% by mass or more, or substantially 100% by mass of the carbon fibers are one or more types selected from the group consisting of PAN-based carbon fibers, pitch-based carbon fibers, thermosetting-based carbon fibers, phenol-based carbon fibers, vapor-grown carbon fibers, and recycled carbon fibers (RCF).

[0038] The type of glass fiber or aramid fiber is not particularly limited. As the glass fiber, for example, glass fibers of various compositions such as E glass, low dielectric glass, silica glass, etc. can be selected and used according to the purpose and use.

[0039] In one embodiment, the reinforcing fibers (C) in the composite material have an average fiber length of 5 mm or more. When the reinforcing fibers (C) have an average fiber length of 5 mm or more, they are also called "continuous fibers." The average fiber length is determined by the arithmetic mean of values ​​measured with a vernier caliper.

[0040] In one embodiment, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, 99% by mass or more, 99.5% by mass or more, or substantially 100% by mass of the composite material is the resin composition and the reinforcing fiber (C).

[0041] The method for producing the composite material (composite method) is not particularly limited. For example, a method of melt-kneading the resin composition with the reinforcing fibers, or a method of melting and impregnating an assembly of reinforcing fibers with one or more forms of the resin composition selected from the group consisting of powder, film, and pellets, can be used. The assembly of reinforcing fibers can be in one or more forms selected from the group consisting of woven fabric, nonwoven fabric, and unidirectional material (also called "UD material"). In these forms, the average fiber length of the reinforcing fibers (C) can be 5 mm or more. That is, the reinforcing fibers (C) can be continuous fibers.

[0042] 3. Molded body The molded article according to one aspect of the present invention is made of the resin composition according to one aspect of the present invention. According to the molded article of this embodiment, since the cohesive failure of the aromatic polyether (A) in the resin composition is suppressed by the interfacial reinforcing agent (B), the molded article of this embodiment has an excellent effect in mechanical strength (e.g., tensile strength). In addition, when the molded article of this embodiment is used in combination with reinforcing fibers, the molded article of this embodiment has an excellent effect in interfacial shear strength to the reinforcing fibers.

[0043] A molded article according to another aspect of the present invention is made of the composite material according to the one aspect of the present invention. According to the molded article of this embodiment, the interfacial shear strength between the resin composition and the reinforcing fibers in the composite material is excellent, and therefore the effect of excellent mechanical strength (for example, tensile strength) can be obtained.

[0044] The shape of the molded article according to one embodiment and another embodiment of the present invention is not particularly limited. In one embodiment, the molded body is an injection molded body, an extrusion molded body, or a compression molded body.

[0045] The applications of the resin composition, composite material, and molded article described above are not particularly limited, and can be widely applied to various applications requiring strength, for example. The resin composition is suitable, for example, as a metal replacement material, particularly for applications requiring heat resistance, solvent resistance, and durability. More specifically, it is suitable, for example, for bearings, gaskets, structural materials, and the like. EXAMPLES

[0046] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0047] Example 1 A 2000 mL four-neck flask equipped with a stirrer, a thermometer, a nitrogen inlet tube, and a water collection container connected to a cooling tube was charged with 285.63 g (1.138 mol) of 4,4'-dichlorobenzophenone (manufactured by Sino-high), 123.40 g (1.121 mol) of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), 159.53 g (1.154 mol) of potassium carbonate (FG-F20 manufactured by AGC Corporation), and 970.30 g of diphenyl sulfone (manufactured by Sino-high), and nitrogen gas was passed through. After the temperature inside the reactor was raised to 150°C, the raw materials were dissolved at 150°C and a stirring speed of 110 rpm. Next, the stirring speed was increased to 250 rpm, and the temperature was raised to 200°C over 30 minutes, held at 200°C for 1 hour, and then raised from 200°C to 250°C over 70 minutes. After holding at 250°C for 1 hour, the temperature was raised from 250°C to 300°C over 110 minutes, and the reaction was further carried out at 300°C for 90 minutes. Thereafter, 22.51 g (0.090 mol) of 4,4'-dichlorobenzophenone was added as a reaction terminator, and the mixture was stirred at 250 rpm for 60 minutes. The contents were then removed into a stainless steel tray and cooled to room temperature to solidify. After the reaction was completed, the product was pulverized in a blender (Waring 7010HS), washed with acetone, an aqueous solution of oxalic acid, and water in that order, and then dried in a dryer at 180°C to obtain a powdered aromatic polyether (A-1) (PEEK). The melt flow rate of the obtained aromatic polyether (A-1) was measured under the following conditions, and the melt flow rate was 15 g / 10 min.

[0048] Melt Flow Rate Measurement The aromatic polyether was subjected to melt flow rate measurement in accordance with JIS K 7210-1:2014 (ISO 1133-1:2011). The results are shown in Table 1. [Melt flow rate measurement conditions] Equipment: Melt indexer (Tateyama Scientific Co., Ltd. L-220) ·Measurement temperature: 380℃ Measurement load (including piston mass): 2.16 kg Cylinder inner diameter: 9.550mm Die inner diameter: 2.095mm Die length: 8.000mm Piston head length: 6.35mm Piston head diameter: 9.474mm (Piston mass: 110.0g) Procedure: The sample was dried at 150°C for at least 2 hours in advance. The sample was placed in a cylinder, the piston was inserted, and preheated for 6 minutes. A load was applied, the piston guide was removed, and the molten sample was extruded from the die. The sample was cut out at a specified range of piston movement and at a specified time (t [s]), and its mass was measured (m [g]). The melt flow rate (MFR) was calculated using the following formula. MFR[g / 10min]=600 / t×m

[0049] Production of resin composition The dry blend raw material obtained by dry blending 100 parts by mass of the obtained aromatic polyether (A-1) and 0.25 parts by mass of the interface reinforcement agent (B) (SI's "Ultranox626", Bis-(2,4-di-tert-butyl-phenyl)-phosphiterythritol diphosphite) was melt-kneaded at a screw rotation speed of 200 rpm and a set temperature of 370 ° C. using a twin-screw extruder having a cylinder diameter of 11 mm (Thermo Fisher Scientific's "Process-11", cylinder volume 20 cc). Here, the dry blend raw material was supplied from the root (upstream side of the screw) of the twin-screw extruder at 7 g per minute. The residence time in the twin-screw extruder was 3 minutes. The strand discharged from the twin-screw extruder was cooled in water and then pelletized using a pelletizer to obtain a resin composition.

[0050] Comparative Example 1 Instead of the aromatic polyether (A-1) obtained in Example 1, an aromatic polyether (A-2) (commercially available PEEK (Victrex, 151G), melt flow rate measured under the same conditions as in Example 1: 36 g / 10 min) was used. A resin composition (pellets) was obtained in the same manner as in Example 1 using 100 parts by mass of the aromatic polyether (A-2) and 0.25 parts by mass of the interface strengthener (B).

[0051] Measurement and evaluation methods (1) Measurement of radical amount The amount of radicals per unit mass of each of the aromatic polyether and the resin composition was measured by an ESR (electron spin resonance) method under the following conditions and procedures. [ESR measurement conditions] ESR device: JESFA200 model manufactured by JEOL Ltd. ·ESR sample tube diameter: 5mm Microwave power: 0.5mW Modulated magnetic field: 0.3mT ·Time constant: 0.03 seconds Magnetic field range: 328~344mT Measurement time: 60 seconds ·Mn strength: 650 ·Measurement temperature: 25℃

[0052] [procedure] TEMPOL (4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl) was dissolved in benzene at a concentration of 5 μM, and 400 μL was added to an ESR sample tube, and ESR was measured under the above measurement conditions. The integral value of the peak derived from TEMPOL obtained was divided by the integral value of the peak of Mn to normalize (integral value A). Then, the measurement sample (aromatic polyether or resin composition) was weighed (weighed value B), filled into an ESR sample tube, and ESR was measured under the above measurement conditions. The integral value of the peak derived from the sample obtained was divided by the integral value of the peak of Mn to normalize (integral value C). Using the obtained values ​​of A, B, and C, the amount of radicals per unit mass of the sample was calculated by the following formula. Radical amount per unit mass of sample [spin / g] = (5 × 10 -6 x400x10 -6 x6.02x10 23 ×C) / (A×B)

[0053] (2) Measurement of interfacial shear strength (microdroplet method) In order to evaluate the interfacial shear strength between the aromatic polyether and the carbon fiber, and the interfacial shear strength between the resin composition and the carbon fiber, the following test was performed using the microdroplet method. The "microdroplet method" is a method for evaluating the interfacial adhesion between a single fiber and a resin by attaching resin particles (droplets) to a single fiber, fixing the droplets, and then performing a pull-out test of the single fiber from the droplets. In the microdroplet method, the interfacial shear strength is calculated from the following formula. τ=F / (πDL) In the formula, τ is the interfacial shear strength [MPa], F is the maximum pull-out load [mN], L is the length of the single fiber embedded in the droplet [μm], and D is the fiber diameter [μm].

[0054] In this example, the interfacial shear strength was measured using a "MODEL HM410" manufactured by Toei Sangyo Co., Ltd., by preparing droplets in a nitrogen atmosphere at a preparation temperature of 370°C, then lowering the temperature to room temperature (25°C), at a pull-out speed of 0.12 mm / min, and a maximum load of 1 N on the load cell. The carbon fiber used was "IM7" manufactured by Hxcel (fiber diameter 5.2 μm). The test was performed 20 times, and the interfacial shear strength [MPa] was calculated from the average value. The larger the value, the better the adhesion to the carbon fiber. The above results are shown in Table 1.

[0055] [Table 1]

[0056] From Table 1, it can be seen that the aromatic polyether of Example 1 has a significantly larger amount of radicals than the aromatic polyether of Comparative Example 1, and is superior in both the interfacial shear strength between the aromatic polyether and the carbon fiber and the interfacial shear strength between the resin composition and the carbon fiber. In addition, in each of Example 1 and Comparative Example 1, the radical amount of the aromatic polyether and the radical amount per unit mass of the resin composition are the same value, which is due to the fact that the amount of the interfacial strengthening agent mixed relative to the aromatic polyether is small.

[0057] Example 2 Composites Manufacturing In the melt kneading using a twin-screw extruder in "Production of resin composition" in Example 1, reinforcing fiber (C) ("TR06U" manufactured by Mitsubishi Engineering Plastics Corporation, chopped carbon fiber, average fiber length 6 mm, filament diameter 7 μm) was fed (side fed) at 3 g per minute from the middle of the twin-screw extruder in the same manner as in Example 1, to obtain a composite material (pellets) containing a resin composition and 43 parts by mass of reinforcing fiber (C) per 100 parts by mass of the resin composition.

[0058] Comparative Example 2 A composite material (pellets) was obtained in the same manner as in Example 2, except that the aromatic polyether (A-1) obtained in Example 1 was replaced with the aromatic polyether (A-2).

[0059] Measurement and evaluation methods Tensile strength measurement The pellets obtained were injection molded using an injection molding machine (Thermo Fisher Scientific "Mini Jet Pro") under conditions of a cylinder temperature of 400°C, a mold temperature of 200°C, and a pressure holding time of 10 seconds to produce ISO527-2-5A tensile test specimens. The tensile strength [MPa] of these tensile test specimens was measured under conditions of a temperature of 23°C and a tensile speed of 2 mm / min. The higher the value, the better the mechanical strength. The results are shown in Table 2.

[0060] [Table 2]

[0061] From Table 2, it can be seen that the composite material of Example 2 is superior to the composite material of Comparative Example 2 in tensile strength.

Claims

1. The standard substance was TEMPOL and the solvent for the standard substance was benzene. The amount of radicals at 25°C was 6.5 x 10 15 ~9.0 x 10 17 The resin composition comprises: an aromatic polyether (A) having a molecular weight of 10 ...

2. The standard substance was TEMPOL and the solvent for the standard substance was benzene. The amount of radicals at 25°C was 6.5 x 10 15 ~9.0 x 10 17 The resin composition according to claim 1, wherein the viscosity is 1000 s / g.

3. The resin composition according to claim 1 or 2, wherein the aromatic polyether (A) is a polyarylene ether ketone.

4. The aromatic polyether (A) comprises one or more selected from the group consisting of polyether ether ketone (PEEK), polyether ketone ketone (PEKK) and polyether ketone (PEK). The resin composition according to any one of claims 1 to 3.

5. The resin composition according to any one of claims 1 to 4, wherein the interface strengthener (B) comprises at least one selected from the group consisting of phosphoric acid compounds, phenolic compounds, amine compounds, and sulfur-based compounds.

6. A composite material comprising the resin composition according to any one of claims 1 to 5 and 0.01 to 500 parts by mass of reinforcing fibers (C) per 100 parts by mass of the resin composition.

7. The composite material according to claim 6, wherein the reinforcing fiber (C) comprises at least one selected from the group consisting of carbon fiber, glass fiber, and aramid fiber.

8. The composite material according to claim 6 or 7, wherein the average fiber length of the reinforcing fibers (C) in the composite material is 5 mm or more.

9. A molded article comprising the resin composition according to any one of claims 1 to 5.

10. A molded article comprising the composite material according to any one of claims 6 to 8.

11. The molded article according to claim 9 or 10, which is an injection molded article.

12. The molded article according to claim 9 or 10, which is an extrusion molded article.

13. The molded body according to claim 9 or 10, which is a compression molded body.

Citation Information

Patent Citations

  • Production of aromatic polyether

    JP1989065129A

  • Method for stabilizing compositions made from poly(arylene-ether-ketone)s (PAEKs)

    JP2023060050A